DYNAMICS OF APPLICATION OF SALUS POPULI SUPREMA LEX ESTO IN LAW ENFORCEMENT IN INDONESIA - Orien Effendi; Ro'is Alfauzi (UNTAG Law Review, 2021)
This paper analyzes the position and legality of the use of principles outside the legal text (unwritten) as the basis for law enforcement in Indonesia. As is known, the sources of law include laws, customs, jurisprudence, and doctrine. So whether the presence of legal provisions outside of legal sources can be used as the basis for law enforcement. This analysis highlights the public assumption that the use of the principle of "Salus Populi Suprema Lex Esto" can be used as a guideline or basis for law enforcement in Indonesia, including when judges use this principle as a basis for decisions. Meanwhile, another opinion states that the principle of "Salus Populi suprema Lex Esto" cannot be used as a reason for law enforcement. Article 12 of the 1945 Constitution states that the president says there is a state of emergency established by law. So that in this case it is not about the principle or source of law which is legal and has legal certainty, but the extent of an emergency so that all provisions in the normal state legal system can be violated.